Investigation the effect of expanded graphite modification on tensile properties and adhesive of epoxy composite - Che Berhanuddin, Nurul Idani (2018)
Graphite has attracted both academia and researchers due to its outstanding properties such as having strength 200 times stronger than steel, great efficiency of heat and electricity conduction, and also low cost. The aim of this study is to determine the tensile properties and adhesive toughness of unmodified graphite composite and to investigate the effects of its modification on the properties of epoxy composite. Two facile approaches of producing the expanded graphite were performed: thermal expansion and sonication process. Since epoxy polymer and graphite are not compatible, thus the interface modifications of graphite are required to enhance the adhesion of filler-polymeric matrix. In this research, 4,4'-Methylene diphenyl diisocyanate (MDI) was used as modifying agent of graphite. The effect of modification on chemical structure, mechanical properties, adhesive toughness and morphology of epoxy composite were investigated by using FTIR, tensile test, double cantilevered beam test and SEM. The results revealed that 0.5 wt% modified composites shows the highest improvement for Young's modulus and adhesive toughness which are 8 GPa and 12.17 kJ/m2 , respectively. These results were also confirmed by the FTIR analysis of the chemical structures and SEM observation of fracture surface. This outcome proved that the surface modifications of expanded graphite have succeeded in enhancing the mechanical properties and improve the adhesive toughness of epoxy composites, hence promote its application as adhesive for metallic adherents.